Correlates of oral health-related quality of life in a sample of patients with rheumatoid arthritis - Fatemeh Babadi; Atefeh Hasanzadeh; Mehdi Aghajari; Mahmood Karimy; Marzieh Araban (BMC Oral Health)
Abstract Background Rheumatoid arthritis (RA) is a prevalent chronic inflammatory joint disease that might exert significant effects on oral health-related quality of life (OHRQoL). This study aimed to investigate OHRQoL in patients with RA. Methods This descriptive-analytical study involved 228 RA patients visiting the Jundishapur Dentistry School, Ahvaz, and dental clinics in Ahvaz, south west of Iran, in 2023. Data collection instruments included a demographic and clinical characteristics form, the Oral Health Impact Profile-14 (OHIP-14), the Health Assessment Questionnaire-Disability Index (HAQ-DI), the General Health Questionnaire (GHQ), and clinical oral examinations. The collected data were analyzed using Spearman’s correlation test and linear regression analysis in SPSS version 22. Results The mean age of the participants was 49.23 ± 10.83 years, and the majority were females. The DMFT index was 14.44 ± 6.63, the mean OHRQoL score was 24.72 ± 5.33, the mean general health score was 5.71 ± 2.21, and the mean disability severity score was 11.62 ± 62.11. Of all variables examined, gender, age, duration of RA, Khuzestan nativity status, smoking, anemia, hyperlipidemia, DMFT index, general health, disability, diabetes, acute kidney disease, and hypertension were significantly associated with OHRQoL(p > 0.05). Conclusion The findings of this study indicate that OHRQoL is compromised in patients with RA. It is recommended that oral health receive greater attention from healthcare professionals managing RA patients and should be taken into account in daily practice of clinicians. Clinicians should develop multi-faceted care including oral health, dental health, general health and quality of life in addition to medical care for RA.